2019
DOI: 10.1152/advan.00043.2019
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of type 2 diabetes mellitus and arterial hypertension content in exercise physiology textbooks

Abstract: de Lira CAB, Viana RB, Luz NF, de Santana MG, Campos MH, Vancini RL, Andrade MS. Analysis of type 2 diabetes mellitus and arterial hypertension content in exercise physiology textbooks. The textbook is a pedagogical tool that provides students and professionals with scientific information. As exercise is an important strategy for the prevention and treatment of noncommunicable diseases, such as type 2 diabetes mellitus (T2DM) and arterial hypertension, the presence of correct and up-to-date scientific informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
0
6
0
4
Order By: Relevance
“…A guiding document was created to allow the analysis of each biology textbook to be organized into a schematic model. This guide was adapted from de Lira et al 7 and the topics addressed in this guiding document were: i) Presence of content that is related to exercise science; ii) presence of misconceptions regarding exercise science; and iii) health benefits provided by physical exercise. All textbooks were carefully investigated in order to locate the text, chapters, or references that addressed the topic of exercise science.…”
Section: Content Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A guiding document was created to allow the analysis of each biology textbook to be organized into a schematic model. This guide was adapted from de Lira et al 7 and the topics addressed in this guiding document were: i) Presence of content that is related to exercise science; ii) presence of misconceptions regarding exercise science; and iii) health benefits provided by physical exercise. All textbooks were carefully investigated in order to locate the text, chapters, or references that addressed the topic of exercise science.…”
Section: Content Analysismentioning
confidence: 99%
“…3,4 Previous studies have shown the presence of misconceptions within high school 5,6 and university textbooks. 7 In regard to biology textbooks, content analysis has suggested the presence of misconceptions, [8][9][10][11][12] and that quality of images, text-image relationships, and its function for learning is affected. [13][14][15] Therefore, teachers should be prepared to deal with any inaccuracies such as misconceptions, decontextualized examples, lack of information, and confusing and complex illustrations, as the students that are exposed to these misconceptions may regard them as being factual.…”
Section: Introductionmentioning
confidence: 99%
“…Estas são de longa duração, afetam a vida do indivíduo (Gyasi et al, 2020) e ameaçam sobrecarregar os sistemas de saúde (World Health Organizaton, 2020), prejudicando o desenvolvimento social e económico em todo o mundo (World Health Organizaton, 2013). A Diabetes Mellitus (DM) tipo 2 e a Hipertensão Arterial (HTA) são DCNT de progressão lenta (Lira et al, 2019) que frequentemente coexistem (Sampanis & Zamboulis, 2008). Os doentes com DM têm duas vezes maior prevalência de HTA, comparando com a população no geral (Sampanis & Zamboulis, 2008;Volpe et al, 2015), sendo a HTA a maior causa de morte prematura no mundo (World Health Organization, 2020), considerada um problema de saúde pública (Radovanovic et al, 2014).…”
Section: Introductionunclassified
“…These are long-term and affect the life of the individual (Gyasi et al, 2020) and threaten to overburden health systems (World Health Organizaton, 2020), hampering social and economic development worldwide (World Health Organizaton, 2013). Type 2 Diabetes Mellitus (DM) and Arterial Hypertension (AH) are slow-progressing NCDs (Lira et al, 2019) that often coexist (Sampanis & Zamboulis, 2008). Diabetic patients have twice the prevalence of AH compared to the general population (Sampanis & Zamboulis, 2008;Volpe et al, 2015), being AH a major cause of premature death worldwide (World Health Organization, 2020) and it is considered a public health problem (Radovanovic et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation